Household finance and consumption survey in Malta: main results of 2010 exercise - Karen Caruana; Christopher Pace (Central Bank of Malta, 2013)
In 2010, the Central Bank of Malta (CBM) carried out a survey to assess households' wealth, financing and consumption in Malta.
Keywords: 330